How communication in organizations is related to foci of commitment and turnover intentions - Holzwarth, Sebastian; Gunnesch-Luca, George; Soucek, Roman; Moser, Klaus (Journal of Personnel Psychology, 2020)

Organizational communication buffers the negative effects of job insecurity on job satisfaction - Holzwarth, Sebastian; Moser, Klaus (Wirtschaftspsychologie, 2019)
Whereas there exists ample evidence of the negative effects of job insecurity on strain (for ex. job satisfaction) less is known about moderating processes. Therefore, we investigate the buffering effect of organizational communication on the relationship between job insecurity and job satisfaction. Moreover, we consider both qualitative (focusing on specific job aspects) and quantitative job insecurity (focusing on the total job) as well as horizontal (communication on the same hierarchical level) and vertical communication processes (e. g.communication across hierarchical levels). We analyzed data from 217 bank account managers (72% female). As expected, both high quality horizontal and vertical communication moderated the negative effects of both forms of job insecurity on job satisfaction. In sum, organizational communication can help to reduce the negative effects of job insecurity on strain (for ex. job satisfaction).